Effect of hydrogen on the fatigue behavior of the near-β Ti-5Al-5Mo-5V-3Cr alloy. (15th April 2017) - Campanelli, Leonardo Contri; da Silva, Paulo Sergio Carvalho Pereira; Jorge, Alberto Moreira; Bolfarini, Claudemiro
Abstract: The influence of hydrogen at low limits on the fatigue behavior of Ti-5553 alloy has been studied. The formation of hydrides was investigated using a high-resolution facility coupled to a transmission electron microscope that provided phase and orientation mappings at the nanometric scale. Besides the fatigue limit reduction for the highest hydrogen content, the predominance of subsurface crack initiation sites with cleavage planes and ductile features in contrast to quasi-cleavage facets in the unstable crack propagation zone suggested the influence of hydrogen. The formation of hydrides, in this case, was attributed to be the reason for the different fatigue behaviors. Graphical abstract: